Twenty Years of VERA: Toward a Universal Facility for Accelerator Mass Spectrometry. (3rd July 2017) - Golser, Robin; Kutschera, Walter
Abstract : With Accelerator Mass Spectrometry (AMS) ultra-low isotopic abundances (10 –12 to 10 –16 ) of long-lived radionuclides, both natural and anthropogenic, are being measured by including an accelerator. Direct atom counting results in an enormous gain in detection sensitivity for long-lived radionuclides as compared to their rare decay. For the most-used radionuclide, 14 C (half-life = 5, 700 yr), this means that instead of grams of carbon required for beta counting one can use milligrams or even micrograms to determine the 14 C content. In addition, an AMS measurement takes less than an hour rather than the several days required for beta counting. The gain becomes even larger for longer half-lives in the million-year range and beyond.